APPLICATION OF ELASTIC-PLASTIC MODEL IN STRESS-STRAIN STATES ESTIMATION OF SOIL MASS - Prusov, Dmitry (Proceedings of National Aviation University (archive), 2006)
The scientific-methodical analysis of a soil mass modelling method by the elastic-plastic model that is used in research findings of heterogeneous and anisotropic material soil mass for their strength and stabilization by the example of system “Plaxis”.